Adhesion compositions with constant tackiness based on butadiene-acrylonitrile rubber. - S. V. Stroilov; L. R. Lusova; V. A. Glagolev (Тонкие химические технологии, 2009)
Adhesion properties of glue compositions with constant tackiness based on butadiene-acrylonitrile rubber and different additives are shown.